Effective Decontamination and Remediation After Elemental Mercury Exposure: A Case Report in the United States - Kelly Johnson-Arbor; Brian Schultz (Korean Society for Preventive Medicine, 2021)
Elemental mercury exposure can result in significant toxicity. Source decontamination and remediation are often required after larger elemental mercury exposures, but the details of these processes are infrequently reported. In the case described herein, a 64-year-old woman and her husband were exposed to elemental mercury in their home after the husband purchased it online for the purpose of recreational barometer calibration. After the mercury reportedly spilled during the calibration process, a vacuum cleaner was used to decontaminate the affected surface; this led to extensive mercury contamination of the home. The couple was relocated from the home while remediation occurred over the course of several weeks. Vacuum cleaning of an elemental mercury spill can lead to extensive volatilization and recirculation of mercury vapor. For smaller mercury spills, careful removal of visible mercury beads by using an eyedropper, cardboard, and masking tape is recommended. Larger spills require professional decontamination and remediation and may necessitate involvement of governmental resources. Vacuum cleaning should not be used as an initial method of decontamination after elemental mercury exposure. Careful attention to source decontamination can reduce the emotional and financial costs associated with extensive remediation after elemental mercury exposure.